Working women’s strategy for work-care balance: the case of University of Dhaka, Bangladesh - Mahboob, Dewan; Rokis, Rohaiza (Ewha Womans University Press, 2014)
The issue of balancing between home and work by working women has received much importance in research around the world. Distinctively, in Bangladesh, a lot of literature on women's issues is focused on less educated women in low-income groups. This article, however, is based on the experiences of highly educated female teaching staff of the University of Dhaka, Bangladesh – one of the oldest public universities in a less developed country – and focuses on the strategies they employ to balance their jobs and family lives. This study concludes that the female teaching staffs of this University place greater emphasis on their families rather than their professional careers, which is not surprising. Nonetheless, their unique strategies of employing several informal flexible practices within the University, in order to maintain a balance between work and care, is indeed a story that needs to be told.